임대인 법정질권의 법역사적 발전 : 민법 제650조의 요건을 중심으로 - 최윤석(Choi, Youn Seok) (법사학연구, 2023)
로마시대의 질권은 점유질과 비점유질 두 가지 유형으로 구분되어 존속하였다. 임대인질권은비점유질로 시작되었다. 임차인이 임차토지에 반입한 물건의 점유를 임대인이 취득하지 않아도임대인질권이 인정되었다. 질권설정에서 일반적으로 요구되는 임대인과 임차인 사이에 임대인질권에 관한 명시적인 합의가 더 이상 필요하지 않는 형태로, 점차 묵시적 합의가 있다는 것을 인정하는 형태로 발전하였다. 유스티니아누스 황제는 임차인이 임차주택에 반입한 물건에 대해서 임대인과 묵시적 합의를 통해 질권이 설정된다는 D. 2,14,4 pr.의 내용을 콘스탄티노플을 넘어서 모든 속주까지 확장하여 적용함으로써 임대인질권을 법정질권으로 발전시켰다. 이 임대인의 법정질권은 보통법과 프로이쎈 일반란트법, 나아가 독일민법 제정과정에서 묵시적합의 조차도 필요 없는 비점유질의 법정질권으로 발전 및 제정되었다. 우리 민법 입법자들은 독일민법을 모범으로 하여 우리 민법전에 임대인 법정질권을 받아들였다. 그러나 우리 민법 제650조는 독일민법과 다르게 건물에 부속한 동산 및 압류라는 요건을 규정하고있는바, 로마시대로부터 발전해 온 비점유질의 임대인 법정질권과는 다른 형태로 변질되어 적용되고 있다. 본 연구는 이러한 문제점에 착안하여 우리 임대인 법정질권의 조화로운 해석을 위해 본제도의 본질을 추적하고, 우리 민법의 문제점과 개선안을 제시하고 있다. The pledge in Roman law was divided into two types: possessory pledge and non-possessory pledge. The lessor’s security right was a non-possessory pledge. The lessor’s security right was accepted even if the lessor did not acquire the possession of the goods brought into the leased land/building by the lessee. Originally, the lessor’s security right was based on an explicit agreement between the lessor and the lessee, which is generally required for the establishment of a pledge. Subsequently, the Roman scholars assumed that the lessor and the lessee agreed implicitly on the lessor’s security right, so that an explicit agreement was no longer required. Justinian I developed the lessor’s security right to a statutory pledge by applying the content of D. 2,14,4 pr. according to which pledges are established through implied agreements on goods brought into the leased apartment by the lessee, beyond Constantinople to all Roman provinces. The lessor’s security right was developed and enacted as a non-possessory statutory pledge which does not require an implied agreement in the Common Law (ius commune), the General State Laws for the Prussian States, and the German Civil Code. The Korean Civil Code accepted the lessor’s statutory pledge in the Korean Civil Code, taking the German Civil Code as an example. Article 650 of the Korean Civil Code reads as follows: “If the lessor of a building or any other structure attaches, pursuant to the claims created under the lease, a movable owned by the lessee and also affixed to the building or any other structure, it shall be effective as a pledge.” Unlike the German Civil Code, Article 650 of the Korean Civil Code stipulates the requirements for movables affixed to the building and their attachment. It differs from the lessor’s statutory non-possessory pledge that has been developed since the Roman law. Focusing on these major differences, this study analyzes the nature and historical development of the lessor’s security right and aims to provide a better legal-historical understanding and an appropriate interpretation of Article 650 of the Korean Civil Code. KCI Citation Count: 0